2013
DOI: 10.1007/s00402-013-1784-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors for allogenic blood transfusion in hip and knee arthroplasty for rheumatoid arthritis

Abstract: The ability to identify those within this high-risk group who are likely to receive blood transfusion allows for an informed, appropriate and cost effective approach to blood management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 21 publications
2
36
0
5
Order By: Relevance
“…Ogbemudia et al investigated preoperative predictors of the need for transfusion in patients undergoing hip and knee arthroplasty (27). They showed that low preoperative Hb, total hip arthroplasty, previous history of myocardial infarction, and previous blood transfusion were significant predictors of the need for allogeneic blood transfusion in the recent procedure; however, their retrospective design restricts implication of their study findings.…”
Section: Discussionmentioning
confidence: 89%
“…Ogbemudia et al investigated preoperative predictors of the need for transfusion in patients undergoing hip and knee arthroplasty (27). They showed that low preoperative Hb, total hip arthroplasty, previous history of myocardial infarction, and previous blood transfusion were significant predictors of the need for allogeneic blood transfusion in the recent procedure; however, their retrospective design restricts implication of their study findings.…”
Section: Discussionmentioning
confidence: 89%
“…Tranexamic acid has been shown to effectively decrease blood loss and postoperative transfusion rates in orthopedic patients without an increase in TEE [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Other studies investigating risk factors for postoperative transfusion found preoperative Hgb to be a significant predictor for subsequent packed red blood cell transfusion [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these investigations demonstrated preoperative Hgb value to be a significant predictor of postoperative transfusion [23][24][25][26]. As such, there are certain preoperative Hgb levels where postoperative transfusion is less likely and the utility of TXA is unknown.…”
mentioning
confidence: 99%
“…Although there are numerous studies of the role of patient and surgical factors on the amount of bone loss in TKA, they are not uniform in their conclusions (2,3). This has been commented by the authors.…”
Section: Discussionmentioning
confidence: 99%